Analysis of Ptun Decision No: 59/G/2021/Ptun-Mdn Regarding the Lawsuit Against the Regent of Deli Serdang Over the Dismissal of Asn: Siyasah Qadhaiyyah Perspective - Putri Eka Ramadhani; Nurhasanah (Warmadewa Press, 2024)
This research analyzes the decision of the Medan State Administrative Court (PTUN) Number: 59/G/2021/PTUN-MDN regarding the Deli Serdang Regent's lawsuit regarding the dismissal of the State Civil Apparatus (ASN) from a siyasah qadhai yyah perspective. Analysis from the siyasah qadhaiyyah perspective is interesting because it can provide insight into how the principles of justice and governance in Islam can be related to modern administrative justice practices. Concepts such as regional al-mazalim (courts to deal with official injustice), the principle of trust in leadership, and the concept of substantive justice in Islam will be analytical frameworks that enrich our understanding of this case. The method used in this research is normative juridical, namely a legal research method carried out by reviewing library materials or secondary data. Data collection techniques were carried out through literature study and data analysis using qualitative descriptive methods. In a broader context, this case also reflects the dynamics of the relationship between regional government and ASN in the era of regional autonomy. This raises questions about the extent to which decentralization of power can affect the protection of ASN's rights and how a system of checks and balances can be implemented effectively at the regional government level. This article aims to analyze the PTUN decision not only from the perspective of Indonesian positive law, but also from the perspective of siyasah qadhaiyyah in Islamic law.